Epidemiological Study of Meningitis Cases Admitted to AL-Razi Hospital in Diyala Governorate for the Period 2000 – 2004 - Abdulsalam H Hassan (Diyala Journal of Medicine, 2019)
Background: Meningitis is an inflammation of the meninges (pia and arachnoids membranes) which covers the brain, it may be either a cute or chronic, purulent or a septic (sterile).  Meningitis  may be caused by  infection  with  viruses , bacteria or other microorganism